Energy efficient node disjoint multipath routing to improve wireless sensor network lifetime - Almazroi, Abdulaleem Ali (Asian Research Publishing Network (ARPN), 2015)
Some of the major challenges confronting wireless sensor networks are usually associated with scarcity of energy and resource limitations. In order to achieve efficient utilization of energy and increase the operational lifetime of the wireless sensor network while at the same time providing consistent packets delivery, energy efficient node disjoint multipath routing was recommended. In our method the nodedisjoint multiple paths are discovered from the source node to the sink node. We make efficient utilization of the network paths by intelligently elect the most suitable paths for packet transmissions based on path cost calculation. The path cost calculation considers the number of hops, minimum energy node in the path and latency rate, As a result the best paths will select based on latest path cost. The structure of the control messages were shown in different categories. The fragmentation of data packets on node-disjoint multipath were also set-up through the network. Results through simulations investigated explains how EENDM accomplished better outcomes than DD and also N-1 multipath routing technique when compared with the benchmarks lifetime of network, control message overhead, consumption of energy node, Packet delivery ratio, and average packet delay.